2020
DOI: 10.1590/1980-57642020dn14-020007
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Argentine version of the Montreal Cognitive Assessment Test (MOCA): A screening tool for Mild Cognitive Impairment and Mild Dementia in Elderly

Abstract: ABSTRACT. The MoCA is a brief useful test to diagnose mild cognitive impairment (MCI) and mild dementia (MD). To date, no Argentine cross-cultural adapted validations of the Spanish version have been reported. Objective: To validate the MoCA in the elderly and study its usefulness in MCI and MD. Methods: This study included 399 individuals over 60 years old evaluated in the Cognitive-Behavioral Department (2017-2018). Patients with<3 years of education, sensory disturbances, psychiatric disorders,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 26 publications
3
22
1
5
Order By: Relevance
“…In addition, results show that on both versions of the MoCA, educational level influences performance coinciding with several studies [20, 23, 28, 30-32]. More importantly, results show that the MoCA Basic continues to be affected by education level in spite of the author’s intentions [35].…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…In addition, results show that on both versions of the MoCA, educational level influences performance coinciding with several studies [20, 23, 28, 30-32]. More importantly, results show that the MoCA Basic continues to be affected by education level in spite of the author’s intentions [35].…”
Section: Discussionsupporting
confidence: 78%
“…The MoCA Full shows a sensitivity of 90% and a specificity of 87% for MCI, and a sensitivity of 100% with a specificity of 87% for mild-stage Alzheimer’s dementia, using a cutoff point of 26 [14]. Similar results have been observed in several studies [5, 9, 13, 16, 17, 20, 23, 25, 36, 37].…”
Section: Introductionsupporting
confidence: 71%
See 2 more Smart Citations
“… 23 In Argentina, MoCA was found to have good accuracy in identifying both MCI and dementia, but it is influenced by educational level. 26 In fact, more comprehensive analyses show MoCA as more suitable for screening for dementia than for MCI. 27 , 28 In Brazil, one study also found that MoCA is the most recommended tool to screen for dementia, but it is not so accurate when screening for cognitive decline before a dementia diagnosis or for low educational levels.…”
Section: Diagnosismentioning
confidence: 99%